Interfacial thermoelectric and mechanical properties of indigenously prepared Ni–Cr–Cu/Co4Sb12 skutterudite thermoelectric joints. Issue 19 (1st October 2022) - Trivedi, Vikrant; Battabyal, Manjusha; Murty, B.S.; Gopalan, Raghavan
Abstract: Thermoelectric and mechanical properties of indigenously prepared Ni–Cr–Cu/Co4 Sb12 skutterudite thermoelectric joints are reported. Co4 Sb12 based skutterudite compounds are highly enticing mid-temperature thermoelectric materials for waste-heat harvesting. Ni–Cr–Cu electrode powder is prepared by ball milling, and a one-step sintering route is adopted to fabricate the Ni–Cr–Cu electrode/n-type Dy0.4 Co3.2 Ni0.8 Sb12 thermoelectric joints. The processed Ni–Cr–Cu/skutterudite joint interface is continuous without having any crack and has low contact resistance (<12 μΩ cm 2 ). The contact resistance at the interface of the joints decreases to 7 μΩ cm 2 under thermal ageing at 823 K for 15 days in a vacuum. The mechanical properties of the joints are not degraded even after ageing at 823 K for 15 days. The theoretical lifetime of the skutterudite device using the Ni–Cr–Cu/Dy0.4 Co3.2 Ni0.8 Sb12 joints is calculated to be 11 years while maintaining the hot side temperature of the device at 773 K. Our results demonstrate that indigenously prepared Ni–Cr–Cu/Co4 Sb12 thermoelectric joints can be effectively used for skutterudite module fabrication.